1-A-D-7. Determining echo intensity by comparison with control muscles. Issue 6 (June 2015) - Matsumoto, Shinichi; Tai, Kaori; Ichimaru, Kanako; Takahashi, Masatoshi; Takamatsu, Naoko
Abstract : Introduction: Determining echo intensity is important for assessing muscle echo, however, it varies with gain, sensitivity time control, etc. Methods: To assess a target muscle, an inspector's biceps muscle was treated as the control muscle. We checked 10 diseased and 10 normal muscles by dual-screen (target muscle and control muscle) and conventional single-screen (target muscle) methods. Three echo beginners examined the target muscle, using a visual analog scale (VAS). We measured intensity differences between target and control muscles, using pixel values from a histogram. Results: Using the dual-screen method, diseased muscle intensity (189.6 ± 28.0 mm, 20.0 ± 21.2) was found to be significantly higher than normal muscle intensity (98.7 ± 42.8 mm; p  = 0.005, −19.8 ± 13.9 mm; p  = 0.007), based on VAS and pixel values. Using the single-screen method, no statistically significant difference was observed between diseased (197.7 ± 62.7 mm) and normal muscles (112.7 ± 71.1 mm, p  > 0.05), based on VAS. However, diseased muscle intensity, based on pixel values (49.8 ± 14.9 mm), was significantly higher than normal muscle intensity (35.0 ± 12.3 mm; p  = 0.047). Discussion: The present analysis suggests that the dual-screen method is adequate for diagnosing muscle echo intensity.